2021
DOI: 10.18203/2320-1770.ijrcog20212170
|View full text |Cite
|
Sign up to set email alerts
|

Tackling gynecological health problems in adolescent girls of rural India: need of the hour

Abstract: Background: Adolescence is a transient and dynamic period characterised by several changes in the child’s body and mind. Onset of menarche is major physiological milestone in adolescent girls which is often associated with menstrual irregularities and other hormonal events. Aim of the present study was to evaluate the profile of adolescent girls attending the outpatient clinic.Methods: This hospital based cross-sectional, prospective, observational study was conducted at Bafna hospital from January 2019 to Dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Abnormal uterine bleeding and excessive bleeding are also widespread among PCOS patients [57,102,118,126]. Some studies [9,112] have revealed that menorrhagia or poly menorrhea were followed by oligomenorrhea or secondary amenorrhea in early teenage girls, whereas the pattern was reversed in the late adolescent group. This demon strates that PCOS is more prevalent in the late teenage group, while puberty menorrhagia is a common symptom in the early adolescent group.…”
Section: Menstrual Dysfunctionmentioning
confidence: 99%
“…Abnormal uterine bleeding and excessive bleeding are also widespread among PCOS patients [57,102,118,126]. Some studies [9,112] have revealed that menorrhagia or poly menorrhea were followed by oligomenorrhea or secondary amenorrhea in early teenage girls, whereas the pattern was reversed in the late adolescent group. This demon strates that PCOS is more prevalent in the late teenage group, while puberty menorrhagia is a common symptom in the early adolescent group.…”
Section: Menstrual Dysfunctionmentioning
confidence: 99%